Quality of Life and Associated Factors in Indonesian Diabetic Patients with Foot Ulcers - Sari, Yunita; Purnawan, Iwan; Taufik, Agis; Sumeru, Annas (Nurse Media Journal of Nursing, 2018)
Background: Diabetic foot ulcer will cause a reduction in quality of life (QOL), high care burden, and even mortality. An assessment of QOL and associated factors in patients with diabetic foot ulcer is important to provide evidence for establishing a care plan program for such patients. However, up to the present, there is no evidence of a published study that investigates the QOL and its associated factors in patients with diabetic foot ulcer in Indonesia.Purpose: The purpose of this study was to investigate the QOL in patients with diabetic foot ulcer in each domain and investigate the factors associated with this condition.Methods: The design of this study was a cross-sectional study. The total sample for this study was 55 patients. The QOL data were collected using a Diabetic Foot Ulcer Scale questionnaire. Statistical analyses were conducted using Mann-Whitney U-test and Kruskal-Wallis test.Results: The result showed that the QOL in the domains of emotions, positive compliance, family life, and friend were high, while the QOL in the domains of daily activities, physical health, leisure, finances, positive attitude, and treatment ranged from low to average. Significant differences were found between income (p=0.004), grade of the wound (p=0.047), number of wounds (p=0.029), and blood glucose (p=0.013) with QOL of patients. Other variables did not have a significant relationship with QOL, but marital status had a significant correlation with the domain of leisure (p=0.004) and duration of the ulcer had a significant correlation with the domain of emotions (p=0.001)Conclusion: There is a correlation between income, grade of the wound, the number of wounds, and blood glucose with QOL of patients with a diabetic foot ulcer. This study recommends to take into account economic status, grade and number of wound, and blood glucose level in order to improve the QOL of patients for an effective patient care plan.